Modelización de un sistema de generación distribuida basada en biogás como fuente de energía - Romo Legña, Diego Fabricio (2015)
The present thesis project develops models to study the use of biogas generated in a landfill, the fuel source for use in motors working for the use of biogas to produce electricity, to be used in a distributed generation approach seeking to optimize the distribution network for reducing line losses, the models are programmed and presented in the MATLAB software tool; first estimation of biogas is modeled by equations degradation, hosted on a municipal solid waste landfill, followed fuel quality is analyzed using a driving machine and determine the most appropriate for use in power generation, once completed one modeling to reduce line losses with the use of distributed generation makes finally a comparative analysis of the emission of polluting gases into the environment is made.